Recent Trends in the Historiography on Warfare in the Colonial Period (1607–1765) - Grenier, John (History compass, 2010)
This essay surveys recent trends (since the mid 1980s) in the historiography on warfare in the Colonial Period (1607-1765). In addition to traditional military history and biography, it focuses on works from the new social military history, ethnohistory, identity studies, and the new frontier and imperial histories. It identifies the current state of the field, as well as areas in need of further research and writing. Teachers can use this essay to contextualize the colonial period’s military history, undergraduate students will find it useful as bibliography/research aid, and graduate students can use it preparing for comprehensive examinations.